(Mis)estimation of the modal number of desired sexual partners. - Arthur G Shapiro; Rubie M Peters; Anthony H Ahrens (PLoS ONE)
Misperceptions of the social world can lead to actions and social policy that are detrimental to an individual's or group's well-being. Here we investigate whether misperceptions arise when participants make predictions of the modal number of ideal future sexual partners reported by heterosexual cohorts (younger cohort: 18-23 years; older cohort: 24-29 years). For both men and women and in both cohorts, the modal number of reported partners equaled 1.0, but men's averages were higher than women's averages due to a subgroup of men who reported desiring large numbers of partners (that is, the distributions had the same shape, but men's distributions had a longer tail). Study 1: When asked to estimate the mode directly, participants performed poorly and, in some conditions, dramatically so (e.g., 40% of younger men reported wanting one sexual partner, but 0% of younger men predicted 1 to be the most frequent response). Study 2: When asked to estimate the shape of the whole distribution, participants underestimated the number of respondents who would desire the mode and thus replicated patterns in the literature for misestimations of skewed distributions. Study 3: When provided information about others' actual modal desired number of partners, the number of male participants who reported desiring one sexual partner increased, suggesting that misperceptions of social norms may influence preferences. We discuss how the mean and mode can lead to two accurate but different interpretations of the data (mean: men report desiring more sexual partners than women; mode: the most frequent response reported by both men and women is 1.0). Discrepancies of this sort can lead to mischaracterizations that may not be uncommon in the research literature. These discrepancies cannot be differentiated by significance tests that seek to find differences in the mean but can be resolved with attention to other methods of analyses.